Performance como texto, escrita como pele - Mattos, Daniela de Oliveira (2013)
This thesis is as much an academic investigation as it is a work of art. It is constituted by text and image mutual crossings, problematizing the artist s writing as a poetic-performative device that produces itself by means of the contiguities that mediate discourse and visuality (and beyond). Conceived of as a space composed of sucessive rectangles, like those filled with words and velocity in the same way as a book , this work also configures itself as a sort of exhibition space or in-between space, which opens room for activations: from the ones, here analyzed, effectuated by the artist s gestures, to the singular experiences that will be generated by each one of the readers, when in contact with what is presented here. The heterogeneous parts that embody this text establish relations to each other, but don t configure a whole; they are not even submitted to hierarchization or evolutive enchainments of any sort, like the ones occurring in accordance with the traditional organization by chapters. Therefore, the research intends to implement and open relations among certain productions of the art field, both from my authorship and from other s, bringing them close to certain works from literature, poetry and philosophy